Posterior approach, fracture diagnosis, and American Society of Anesthesiology class III-IV are associated with increased risk of revision for dislocation after total hip arthroplasty: An analysis of 33,337 operations from the Finnish Arthroplasty Register - V. J. Panula; E. M. Ekman; M. S. Venäläinen; I. Laaksonen; R. Klén; J. J. Haapakoski; A. P. Eskelinen; L. L. Elo; Keijo T. Mäkelä (SAGE PUBLICATIONS LTD, 2022)
Background and Aims:
Dislocation is one of the most common reasons for revision surgery after primary total hip arthroplasty. Both patient related and surgical factors may influence the risk of dislocation. In this study, we evaluated risk factors for dislocation revision after total hip arthroplasty based on revised data contents of the Finnish Arthroplasty Register.Materials and
Methods:
We analyzed 33,337 primary total hip arthroplasties performed between May 2014 and January 2018 in Finland. Cox proportional hazards regression was used to estimate hazard ratios with 95% confidence intervals for first dislocation revision using 18 potential risk factors as covariates, such as age, sex, diagnosis, hospital volume, surgical approach, head size, body mass index, American Society of Anesthesiology class, and fixation method.
Results:
During the study period, there were 264 first-time revisions for dislocation after primary total hip arthroplasty. The hazard ratio for dislocation revision was 3.1 (confidence interval 1.7-5.5) for posterior compared to anterolateral approach, 3.0 (confidence interval 1.9-4.7) for total hip arthroplasties performed for femoral neck fracture compared to total hip arthroplasties performed for osteoarthritis, 2.0 (confidence interval 1.0-3.9) for American Society of Anesthesiology class III-IV compared to American Society of Anesthesiology class I, and 0.5 (0.4-0.7) for 36-mm femoral head size compared to 32-mm head size.
Conclusion:
Special attention should be paid to patients with fracture diagnoses and American Society of Anesthesiology class III-IV. Anterolateral approach and 36-mm femoral heads decrease dislocation revision risk and should be considered for high-risk patients.